Development of new PTK7-targeting aptamer-fluorescent and -radiolabelled probes for evaluation as molecular imaging agents: Lymphoma and melanoma in vivo proof of concept. Issue 3 (1st February 2017) - Calzada, Victoria; Moreno, María; Newton, Jessica; González, Joel; Fernández, Marcelo; Gambini, Juan Pablo; Ibarra, Manuel; Chabalgoity, Alejandro; Deutscher, Susan; Quinn, Thomas; Cabral, Pablo; Cerecetto, Hugo
Graphical abstract: Abstract: Aptamers are single-stranded oligonucleotides that recognize molecular targets with high affinity and specificity. Aptamer that selectively bind to the protein tyrosine kinase-7 (PTK7) receptor, overexpressed on many cancers, has been labelled as probes for molecular imaging of cancer. Two new PTK7-targeting aptamer probes were developed by coupling frameworks from the fluorescent dye AlexaFluor647 or the 6-hydrazinonicotinamide (HYNIC) chelator-labelled to 99m Tc. The derivatizations via a 5′-aminohexyl terminal linker were done at room temperature and under mild buffer conditions. Physicochemical and biological controls for both imaging agents were performed verifying the integrity of the aptamer-conjugates by HPLC. Recognition of melanoma (B16F1) and lymphoma (A20) mouse cell lines by the aptamer was studied using cell binding, flow cytometry and confocal microscopy. Finally, in vivo imaging studies in tumour-bearing mice were performed. The new probes were able to bind to melanoma and lymphoma cell lines in vitro, the in vivo imaging in tumour-bearing mice showed different uptake behaviours showing for the fluorescent conjugate good uptake by B cell lymphoma while the radiolabelled conjugate did not display tumour uptake due to its high extravascular distribution, and both showed rapid clearance properties in tumour-bearing mice.